2017
DOI: 10.1007/978-3-319-55550-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Sampling and Systems from Iterative Actions of Operators

Abstract: In this chapter, we review some of the recent developments and prove new results concerning frames and Bessel systems generated by iterations of the form {A n g : g ∈ G, n = 0, 1, 2, . . . }, where A is a bounded linear operator on a separable complex Hilbert space H and G is a countable set of vectors in H . The system of iterations mentioned above was motivated from the so called dynamical sampling problem. In dynamical sampling, an unknown function f and its future states A n f are coarsely sampled at each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 22 publications
2
51
0
Order By: Relevance
“…Therefore T can be extended to a bounded operator on H, as claimed. The proof shows that ||T || ≤ √ BA −1 ; the inequality ||T || ≥ 1 is proved in [4]. in Example 1.1.…”
Section: Boundedness Of the Operator Tmentioning
confidence: 84%
“…Therefore T can be extended to a bounded operator on H, as claimed. The proof shows that ||T || ≤ √ BA −1 ; the inequality ||T || ≥ 1 is proved in [4]. in Example 1.1.…”
Section: Boundedness Of the Operator Tmentioning
confidence: 84%
“…Hence, the spectrum of a strongly stable operator T is contained in the closed unit disk. It is, moreover, quite easily shown that neither T nor T * can have eigenvalues on the unit circle T. The first statement of the following lemma was proved in [5]. Lemma 3.1.…”
Section: Dynamical Sampling With General Bounded Operatorsmentioning
confidence: 97%
“…Concerning the infinite-dimensional situation, the most interesting result in [3] addresses the one-vector problem (i.e., |I| = 1). This result was further improved in [2] and [5]. Its final version reads as follows: If A is a normal operator, the system (A n f ) n∈N is a frame for H if and only if (a) A = inN λ j · , e j e j with an ONB (e j ) j∈N , (b) the sequence (λ j ) j∈N is uniformly separated in the unit disk (cf.…”
Section: Previous Work On the Topic And Our Contribution The Histormentioning
confidence: 98%
See 1 more Smart Citation
“…We will close the paper with a few operator-theoretical considerations, to which we have referred throughout the paper. 1) Instead of representing a frame on the form {T k f 0 } k∈Z , one could also consider representations on the form {T n f 0 } ∞ n=0 ; this indexing occur, e.g., in dynamical sampling [2,3]. The chosen indexing actually has a serious influence on the properties of the operator T. For example, there exist frames {f k } k∈Z = {T k f 0 } k∈Z where T is a unitary operator (Example 1.1); but if we reindex the frame as {f k } ∞ k=0 it can not be represented on the form {U n f 0 } ∞ n=0 for a unitary operator U, see [3].…”
Section: Appendix: Auxiliary Examplesmentioning
confidence: 99%